PENGARUH GERAKAN 3R (REDUSE, REUCE, RECYCLE) TERHADAP PENINGKATAN KESADARAN SISWA PADA PEMBELAJARAN PENDIDIKAN LINGKUNGAN HIDUP DI KELAS III SDN 4 JALAKSANA - Tina Agustin; Neng Lia Yulianengsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of the 3R (Reduce, Reuse, Recycle) movement on increasing student awareness in Environmental Education learning in grade 3 of SDN 4 Jalaksana. The main problem faced by SDN 4 Jalaksana is that good waste management has not been implemented, due to the lack of programs and learning that focus on waste management. This study used the Pre-Experimental method with a One-Group Pretest-Posttest design. The research sample consisted of 21 grade 3 students of SDN 4 Jalaksana. Data collection was carried out through questionnaires, and data analysis included validity, reliability, and analysis prerequisite tests. The results showed a significant increase in student awareness of waste management after the implementation of the 3R movement. This proves that the 3R movement can be an effective approach in increasing student awareness of sustainable waste management.